Substituted heterocycles as new candidates for liquid organic hydrogen carriers: In silico design from DFT calculations (2021)
A new set of compounds based on N- and S-heterocycles were investigated through Density Functional Theory (DFT) for their use as liquid organic hydrogen carriers (LOHCs). The hydrogenated forms of these compounds could release hydrogen within the most important technical requirements in mobile and stationary applications. In this work, the potential of the 1H-pyrrole/tetrahydro-1H-pyrrole and thiophene/tetrahydrothiophene pairs as possible leader structures to synthesize more sustainable LOHCs from costless oil-refining and oil-hydrotreating by-products is shown. According to DFT-M06-HF results, the 3-allyl-1H-pyrrole/3-allyl-tetrahydro-1H-pyrrole pair presented an adequate theoretical hydrogen storage capacity (3.6 %wt H) and a high theoretical dehydrogenation equilibrium yields (% εd = 67.8%) at 453 K. Therefore, this pair is recommended for hydrogen storage stationary applications. On the other hand, the 2-(thiophen-2-yl)-1H-pyrrole/2-(2,3-dihydrothiophen-2-yl)tetrahydropyrrole pair proved to be suitable for both mobile and stationary applications; the storage capacity of this pair was 3.9 %wt H and the theoretical dehydrogenation equilibrium yields at 453 K (% εd = 28.1%) was considered moderate.